Evaluation of a hub-and-spoke model for the delivery of femtosecond laser-assisted cataract surgery within the context of a large randomised controlled trial. Issue 11 (7th February 2018) - Roberts, Harry W; Wagh, Vijay K; Mullens, Isabella J M; Borsci, Simone; Ni, Melody Z; O'Brart, David P S
Abstract : Aims: To test a hypothesis that cataract operating room (OR) productivity can be improved with a femtosecond laser (FL) using a hub-and-spoke model and whether any increase in productivity can offset additional costs relating to the FL. Methods: 400 eyes of 400 patients were enrolled in a randomised-controlled trial comparing FL-assisted cataract surgery (FLACS) with conventional phacoemulsification surgery (CPS). 299 of 400 operations were performed on designated high-volume theatre lists (FLACS=134, CPS=165), where a hub-and-spoke FLACS model (1×FL, 2×ORs=2:1) was compared with independent CPS theatre lists. Details of operative timings and OR utilisation were recorded. Differences in productivity between hub-and-spoke FLACS and CPS sessions were compared using an economic model including testing hypothetical 3:1 and 4:1 models. Results: The duration of the operation itself was 12.04±4.89 min for FLACS compared with CPS of 14.54±6.1 min (P<0.001). Total patient time in the OR was reduced from 23.39±6.89 min with CPS to 20.34±5.82 min with FLACS (P<0.001)(reduction of 3.05 min per case). There was no difference in OR turnaround time between the models. Average number of patients treated per theatre list was 9 for FLACS and 8 for CPS. OR utilisation was 92.08% for FLACS and 95.83% for CPS (P<0.001). Using a previously established economic model, the FLACS service cost £144.60 more than CPS per case. This difference would be £131 and £125 for 3:1 and 4:1 models, respectively. Conclusion: The FLACS hub-and-spoke model was significantly faster than CPS, with patients spending less time in the OR. This enabled an improvement in productivity, but insufficient to meaningfully offset the additional costs relating to FLACS.